Late pruning: an alternative for adapting viticulture to climate change? - Salazar-Parra, Carolina; Reyes, Marisol; Peppi, Cecilia (Revista Mexicana de Ciencias Agrícolas, 2023)
The quality and production of the vine depend on the climate; therefore, changes in it can affect its sustainability. For Chile, an increase of at least 1 °C in temperatures in the Central Valley has been projected, which can directly affect the ripening process of vines, accelerating the accumulation of sugars, affecting organic acids, and decreasing phenolic compounds, which translates into an imbalance of ripening. Considering this, to ensure the sustainability of viticulture in the face of climate change, management alternatives that allow optimal ripening in the face of changing climatic conditions are sought. One of these alternatives is late pruning. Late pruning proposes to delay the pruning dates after bud break and before flowering, eliminating the reserves already mobilized in the plant, thus generating a phenological delay. This delay in growth would allow for less accelerated ripening. To assess the effectiveness of this technique, three pruning dates: traditional pruning (TP), pruning at bud break (BP), and pruning in 2-3 leaves (LP), were evaluated in a commercial vineyard of the cv Cabernet Sauvignon in the Central Valley during the 2020-2021 season. The preliminary results of this study show positive expectations of this technique, delaying the phenology of the crop and the harvest dates. However, this seems to depend on the phenological moment where late pruning is performed and the varietal characteristics. The BP presented a delay of the harvest time of six days without affecting the production or the initial quality of the berries. Likewise, the LP affected the set of bunches and did not delay the harvest. The results showed that it is possible to delay harvest dates; nevertheless, it is relevant to consider other variables such as variety, phenological moment, soil, and climate.
Keywords: Vitis vinifera; climate change; imbalance; phenology; pruning; ripeness; temperature